Influence of long-term cold climate operation on structure, fatigue durability and impact toughness of 09Mn2Si pipe steel; Engineering Failure Analysis; Vol. 102 - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Marushchak P. O. Pavel Orestovich; Eremin A. V. Aleksandr Vyacheslavovich; Berto F. Filippo; Syromyatnikova A. S. Aytalina Stepanovna; Vinogradov A. Yu. Aleksey Yurjevich (2019, 2019)
Title screen